Responses to Heat Stress Within an Unplanned Settlement in Dar Es Salaam, Tanzania - Adegun, Olumuyiwa Bayode; Mbuya, Elinorata Celestine; Njavike, Emmanuel (Frontiers in Built Environment, 2022)
Addressing the fallouts of a +1.5oC world is one of the key challenges for urban management in African cities. This paper reports a work dealing with climate adaptation in informal urban settlements, with . The focus here is on responses to heat stress among the urban poor. The study involved a survey of The results presented emanated a survey of the 405 residents in Keko Mchungwa – an unplanned neighbourhoods in Dar es Salaam, Tanzania. We found that, the most popular behavioural responses are taking a shower; wearing light clothing; cold drinks; opening doors and windows. The rarest forms of responses, which are swimming and contributing to savings group. Heat-related health problems experienced by the residents were also identified. Enhancing human responses to heat stress will involve demands improvement in basic services and infrastructure, awareness and education among the residents.